ANALISIS PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA) DAN RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - B11110150, SARTONO (Jurnal Manajemen Update, 2015)
The purpose of this research is to examine and analyze the influence of Economic Value Added (EVA), Market Value Added (MVA)andReturn On Asset (ROA) onStock Return ofconsumer goods companieslisted in Indonesia Stock Exchange from the period 2011-2013. The kind of this research is quantitativeresearch. The samplein this research are 13 consumer goods companies that selected with purposive sampling. The collect data method is documentation study.Data analyzed with multiple linear regression method. Result of this research indicated that Economic Value Added (EVA), Market Value Added (MVA) had not a significant effect to Stock Return, and Return On Asset (ROA) had a significant effect to Stock Return.Determinant coefficient (R2) is 0.198, means 19.8% of Stock Returnchange is affected byEconomic Value Added (EVA), Market Value Added (MVA)andReturn On Asset (ROA) while the remaining is influenced by others factors which are not taken into account in the model of analysis. Keywords : Economic Value Added (EVA), Market Value Added (MVA),Return On Asset (ROA) and Stock Return.